Southeast Florida large Orbicella faveolata are highly fecund without evident disease intervention effects - Renegar, D. Abigail; Noren, Hunter K. G.; Turner, Nicholas R.; Figueiredo, Joana; Walker, Brian K. (Frontiers in Marine Science, 2024)
The recent widespread mortality and tissue loss in Florida from stony coral tissue loss disease (SCTLD) has propelled the need for assisted reproduction to restore reefs, especially for the ESA listed species Orbicella faveolata. In situ gamete collection can be challenging due to the weather and resources (boats and divers) required during the expected spawning window. In the northern portion of the Florida coral reef tract, coral spawn collection has been even more difficult due to historical inconsistency in annual spawning times and the potential for “zombie” corals, i.e. large but reproductively senescent individuals. Therefore, we examined the current reproductive potential of seven large (>2 m diameter) O. faveolata colonies from this region, quantified their fecundity, and estimated the spawning timeframe using histology. Additionally, we explored whether previous SCTLD lesion amoxycillin treatments affected reproductive metrics. Understanding the reproductive capacity and spawning timing of these large corals, given their history of disease and disease treatment, is critical to evaluate potential impacts of SCTLD treatments and the success of assisted reproduction efforts. The histological analysis coupled with in-water observations indicated a probable split-spawn in these individuals in 2020, although the dates of spawning may not be consistent with predictions for the wider Caribbean or with other colonies in Miami and the Florida Keys. All seven large O. faveolata colonies were found to contain abundant oocytes, with no obvious impact of SCTLD treatments on gamete development or fecundity.